KUALITAS SEMEN BABI RAS PERSILANGAN PADA TIGA BREED BERBEDA DALAM SUHU PENYIMPANAN YANG BERAGAM (Semen Quality of Crossbred Boars from Three Different Breeds at Different Storage Temperatures) - G. A. Septiana; N. L. G. Sumardani; I N. T. Ariana (Universitas Nusa Cendana, 2026)
Spermatozoa motility and viability are key determinants of semen suitability for artificial insemination. The values of motility and viability are influenced by treatments applied before and after semen dilution. This study aimed to evaluate the semen quality of boars from different breeds under varying storage temperatures. The research was conducted at the Animal Reproduction Laboratory, for one month, using a completely randomized factorial split-time design. The first factor was breed (B), consisting of three crossbred boar breeds: B1 (Landrace Crossbred), B2 (Duroc Crossbred), and B3 (Yorkshire Crossbred). The second factor was storage temperature (S), comprising three levels: S1 (18°C), S2 (20°C), and S3 (22°C). Each treatment was replicated three times, and semen quality (spermatozoa motility and viability) was evaluated after storage for T1 (1 day), T2 (2 days), and T3 (3 days). The results showed that breed had a significant effect (P<0.05) on spermatozoa motility and viability, whereas storage temperature (18°C, 20°C, and 22°C) had no significant effect (P>0.05). No interaction was observed between breed and storage temperatures on semen quality. Yorkshire Crossbred Boars (B3) exhibited the best semen quality, as spermatozoa were able to maintain motility of 61.93% and viability of 79.19% after 3 days of storage (T3).